Geographical of analysis of the health services in Al-shattrah for ( 2018 ) - Latif J Farhan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
This research aims to study and analyze the current medical status in the center of Al-Shattrah district from geographical point of view for the year 2018 quantitatively qualitatively , as well as , the population of people In this study researchers discovered there was a salient deviation in spatial distribution for medical sectors comparing with ratio of population this resulted in or reflected in clear disability of presenting medical services This study has essential points the first is geographical distribution for medical institutions in the downtown in addition to private pharmacies which belong to the same doctors The second point focuses on the proficiency of these medical institutions and their services for this town within special standards